Pendidikan Kesehatan Pada Keluarga TN. S Untuk Merubah Pengetahuan Sikap Perilaku Tentang Nutrisi - Kusuma, Anggar Tira, Agus Sudaryanto, S.Kep., Ns., M.Kes (2016)
Background: The condition of insufficience of nutrition will have a bad effect on health. The insufficience of nutrition is well known as malnutrition or lack of nutrition. Malnutrition or lack of protein energy is a dangerous problem, if it is not seriously handled, it causes a developmental disturbance. The developmental disturbance is suffered by a malnutrition child, in which the children has difficulty to concentrate and has very bad coordinations of his/her sensory and motor. Besides the developmental disturbance, the growth disturbance also occurs in a malnutrition child. The growth disturbance in the malnutrition child which often occurs are the weight and the height of the child are under the normal standard or not being similar to the common children. Objective: To increase the knowledge on nutrition and to implement nursing on the sick family member based on family nursing. Method: This method used a descriptive method through a case study which is by collecting data, analyzing data and drawing conclusion based on the data. Results: The actions provided to the family was the health education on malnutrition disease which aimed at knowing the problem and the family could solve the problem they faced. The writer also gave explanation on balanced nutrition, explained and educated on how to make modisco to help increasing the weight and as a diet menu everyday. Conclusion: Health education for family can give influence on knowledge, attitude, and behavior. The giving of additional recovery foods (PMT-P) is needed to add energy and protein such as modisco as one of example, which is made of skim milk, sugar, and oil.